Design of Energy Management System Base on lithium-ion Battery - Saleh, Yusuf Bello; Kürüm, Hasan (Osman SAĞDIÇ, 2021)
Yeşil enerjiyi kullanmak günümüz dünyasında giderek daha önemli hale gelmektedir. Hava kirliliği nedeniyle elektrikli araçlar şu anda çevre, kişisel ve toplu taşıma için en iyi seçimdir. Elektrikli araçlarda kullanılan piller, güvenli bir çalışma alanında kullanılmadıkları takdirde tehlikeli olabilir. Bu çalışmanın amacı, pil paketindeki her hücrenin gerilimini, akımını, hücre dengelemeyi ve paketin sıcaklığını izleyebilen bir batarya yönetim sistemi (BYS) tasarlamaktır. Bunun için, sistemin donanımını ve işleyişini değerlendirmek amacıyla sistemin örnek bir test bileşeninin geliştirilmesi gerekir. Elektrikli araçların, güvenlikleri operasyonel alan (GOA) içerisinde her zaman kontrol altında tutulmalıdır. İstenen gerilim ve kapasiteyi elde etmek için birden fazla pil hücresi birleştirilir. Elektrikli arabalar için gereken yüksek gerilim ve kapasiteye ulaşmak için çok sayıda hücreye ihtiyaç vardır. Bu tezde, her bir pil hücresinin işlevini izleyerek kötü hücreleri tespit etmek ve bu hücreleri pil paketinde değiştirmek üzere bir algoritma geliştirilmiştir. Bu hücrelerin durumu LCD ekranda gözlenmiştir.

In today's world, green energy is becoming increasingly important. Due to air pollution, electric vehicles are currently the greatest option for the environment, personal and public transportation. Electric vehicles need batteries, which might be hazardous if they are not used in a safe atmosphere. The purpose of this work is to develop a battery management system (BMS) prototype that can track the voltages, currents, and cell balancing of each cell in a battery pack, as well as the temperature of the pack. The batteries in electric vehicles must always be kept under control within their operational safety area (SOA). To achieve the desired voltage and capacity, multiple battery cells are joined. A huge number of cells are necessary to provide the high voltage and capacity required for electric vehicles. This paper developed methods for monitoring each battery cell's functionality and Algorithms for detecting bad cells for replacement in the battery pack and displaying those cells condition on the monitor whether they are good or bad to notify the users, the current conditions of each cell for the user's next line of action. The experiment was carried out using STM32 microcontrollers.
Design of Energy Management System Base on lithium-ion Battery
Keywords: Engineering; Mühendislik